RACE AND RISK: EXPLORING ONLINE RESPONSES TO THE EURO 2020 FINAL - Rosamond, Emily (AoIR Selected Papers of Internet Research, 2023)
In July 2021, England lost the Euro 2020 football final to Italy. Following the loss, Black England players were widely racially abused online. As Twitter took down over 1900 offensive posts directed at the players, and commentators condemned the racism, sending supportive messages to players, the controversy continued to generate traffic. How might online platforms reconfigure racism, according to a late-neoliberal logic of assetized attention and identity? How might the football game, as a widely publicized symbolic site which stages a relation between competition, chance, and nationhood, inflect these expressions of racism? In this paper, I analyze online responses to the 2020 Euro finals, with a focus on narratives expressing expectations about posters’ and platforms’ roles in propagating online racism. I analyze how online platforms express conflicts over race in the reputational terms of status and attention metrics. Extending insights from W.E.B. Du Bois, Cedric Robinson, and Cheryl Harris, I arrive at an account of assetized, late-neoliberal racial capitalism, which recodes racism as the uneven distribution of reputational risk.